Pengembangan Media Pembelajaran Puzzle Pada Materi Sel Kelas X SMA - Dini Afriansyah (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2023)
This development research aims to determine the validity, practicality and effectiveness oflearning media puzzle on cell material. This research method uses the R&D method with the development model of Rowntree, namely planning and development, then using the evaluation stages of the Tessmer (1993) model, namely self-evaluation, expert review, one- to-one, and small group evaluation. Data collection techniques using techniques walkthrough and questionnaires. The data analysis techniques used were walkthrough data analysis and questionnaire data analysis. The sample population in this study were students of class X. The data were analyzed using Microsoft Excel and SPSS 22 programs. This can be seen from the results of this study which indicate that thelearning media is puzzle classified as a very valid category with an average of 90%, very practical with an average value of 88% and alsolearning media puzzle thisis very effective. Based on the results of pre-test and post-test the students'by obtaining a hypothesis (t-test), it shows that the significant value is less than 0.05 (0.000 <0.05). then Ha is accepted and H0 is rejected, which means thatlearning media puzzle thisis effective for use in the learning process. The learning process in cell material is felt to be more effective and learner-centered which makes students more active in learning and makes the learning process more meaningful. If the learning response is good, it can be used to improve student learning outcomes.